Isotype Switching Increases Efficacy of Antibody Protection against Staphylococcal Enterotoxin B-Induced Lethal Shock and Staphylococcus aureus Sepsis in Mice - Varshney, Avanish K. (American Society of Microbiology, 2014)
Staphylococcal enterotoxin B (SEB) is a potent toxin that is produced by Staphylococcus aureus strains and is classified as a category B select agent. We have previously shown that monoclonal antibody (MAb) 20B1, a murine anti-SEB IgG1, successfully treats SEB-induced lethal shock (SEBILS) and bacteremia that is caused by SEB-producing S. aureus. In this study, we have generated two isotype switch variants of the original IgG1 MAb 20B1, an IgG2a and IgG2b, both bearing the same variable region sequence, and compared their neutralizing and protective activity in in vitro and in vivo assays, respectively. All 3 isotypes demonstrated comparable affinity to SEB and comparable 50% inhibitory concentrations (IC(50)s) in T cell proliferation assays. In vivo, however, the IgG2a isotype variant of 20B1 exhibited significantly greater protection than IgG1 or IgG2b in murine SEB intoxication and S. aureus sepsis models. Protection was associated with downmodulation of inflammatory host response. Our data demonstrate that changing the isotype of already protective MAbs, without affecting their antigen specificity or sensitivity, can result in an enhancement of their protective ability. Isotype selection, therefore, should be carefully considered in the development of toxin-neutralizing MAbs and the design of antibody therapeutics.